Profil Kreativitas dan Ketrampilan Bekerja Ilmiah pada Konsep Asam, Basa, dan Garam Siswa - Sidon Dina Agustina; Joko Siswanto (Media Penelitian Pendidikan : Jurnal Penelitian dalam Bidang Pendidikan dan Pengajaran, 2021)
This study aims to analyze the creativity and scientific work skills of Grade VII students of SMP Negeri 1 Ampelgading on the concepts of acid, base and salt. This study uses a test method, the determination of the sample is class VII a number of 32 students, creativity from the category of not creative, less creative, creative and very creative respectively at 6.65%; 39.57%; 53.78%; 0.00%. In the analysis of scientific work skills data from the unskilled, less skilled, skilled and highly skilled categories respectively 4.63%; 38.52%; 55.55%; 1.3%. There is a difference in the presentation between students' creativity and scientific work skills.